Ijtihad dalam pelaksanaan ibadat: Analisis terhadap beberapa ibadat terpilih / Amran Dingdorrormaeng - Amram , Dingdorrormaeng (2019)
This study aims to explain the status of ijtihad in the implementation of worship, and the role of ijtihad which is justified in the aspect of worship. The study also searches for answers to cases that are considered as new forms of worship currently, in order to convince the Muslim community to practice it. In addition, this study also attempts to clarify the validity of the worship, whether it has a solid foundation of legal aspects or otherwise. Furthermore, this study also discusses the principles of maqāṣid al-sharī‘ah used in the aspect of worship, either from the views or ijtihad of certain scholars.The study encompasses the concept of ijtihad in Islamic law, scholar’s view of ijtihad in worship, legal sources and ḍawābiṭ used by mujtahidin. The method used by the scholars in the determination of the law of worship which had never been done by the Prophet.The result of this study found that there are aspects in worships which ijtihad is permitted. Ijtihad in worship has indeed occurred mainly in certain rituals that are not clearly specified by the Lawgiver that which fall under the general principles sharī’ah.. The ijtihad in the domain of worship mainly applies the qiyās and other instruments together with certain well-established ḍawābiṭs in sharī’ah.